2010 IEEE International Symposium on Parallel &Amp; Distributed Processing, Workshops and PHD Forum (IPDPSW) 2010
DOI: 10.1109/ipdpsw.2010.5470840
|View full text |Cite
|
Sign up to set email alerts
|

Efficient traffic simulation using the GCA model

Abstract: The GCA (Global Cellular Automata) model consists of a collection of cells which change their states synchronously depending on the states of their neighbors like in the classical CA (Cellular Automata) model. In contrast to the CA model the neighbors can be freely and dynamically selected at runtime. The GCA model is applicable to a wide range of parallel algorithms. We present a mapping of the the well known Nagel-Schreckenberg algorithm for traffic simulation onto the GCA model using agents. The vehicles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…FPGAs have demonstrated performance benefits when applied to CA-based models such as an environment simulation [15], Game of Life [4] and a crowd evacuation model [6]. Schäck et al [12] implement a traffic simulation on a single lane road based on so-called Global CA model in which a set of cells change their states simultaneously. Tripp et al [14] develop a CA-based traffic simulation running on a grid of roads.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…FPGAs have demonstrated performance benefits when applied to CA-based models such as an environment simulation [15], Game of Life [4] and a crowd evacuation model [6]. Schäck et al [12] implement a traffic simulation on a single lane road based on so-called Global CA model in which a set of cells change their states simultaneously. Tripp et al [14] develop a CA-based traffic simulation running on a grid of roads.…”
Section: Related Workmentioning
confidence: 99%
“…It has been demonstrated that FPGAs can outperform CPUs or GPUs, e.g., in data encryption [2]. Previous works [12,14] also show the feasibility of accelerating ABTSs using FPGAs. Those works often rely on converting common traffic models to models based on Cellular Automata (CA), which naturally map to the FPGA's hardware building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Several different architectures and enhancements for the GCA model have been developed [14,15,16,17,11,12]. While the GCA model can be used for many different applications our focus is the simulation of MAS.…”
Section: Agent System Layermentioning
confidence: 99%
“…traffic simulation [13], simulation of biologic systems [21,18] or ecosystems [5]. In previous work [15,17] we have shown how multiagent systems (MAS) can be described and simulated using the GCA (Global Cellular Automata) model [9,10]. Other investigations have incorporated the characteristics of CAs (Cellular Automata) to simulate HIV-Immune Interaction Dynamics [24].…”
Section: Introduction and Related Workmentioning
confidence: 99%